SPATIAL COMPARISON OF THE LEVEL AND RATE OF CHANGE OF FARM INCOME IN THE YEARS 2004-2012 - Stanisław Jaworski (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The primary aim of this paper is to determine the income changes in agricultural regions in the period from 2004 to 2012. In the first part of the paper, we have summarised the income dynamics in various provinces in Poland. The dynamics is elaborated in terms of income’s level, pace and acceleration. In the second part, we take into account some predictor variables. We have investigated the time-varying impact on income using a functional concurrent regression model. We used data from the Polish FADN. Our conclusions relate to 50% of typical farms in Poland in terms of the time-varying mean income of provinces. The analysis was performed in the R-CRAN.